Pemaknaan Hidup (Meaning in Life) dalam Kajian Psikologi - Fridayanti Fridayanti (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2013)
This article is the result ofcontemplation about the concept ofmeaning of life. The meaning of life is very important in optimizing the function of humanity, especially when faced to a situation that is full load and pressure. The concept of meaning of life affects individual well-being and happiness. Psychologists, particularly positive psychologists, has been trying to formulate the concept of the meaning of life, however, the breadth and complexities of life make meaning of the concept definition and operationalization of this concept to be very diverse. This article gives an overview of the breadth of understanding of the meaning of life, definition, and operationalization of the meaning of life which has been formulated by experts.Keyword: meaning in life, situational meaning, personal meaning